2021
DOI: 10.1002/jtr.2479
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the role of constraints and motivations behind traveling in the prediction of destination choice: Evidence from PLS‐SEM and fsQCA

Abstract: This study aims to examine the relationship among travel constraints, travel motivations, and destination choice via a multi-method approach. For this purpose, two studies and two analysis tools-PLS-SEM and fsQCA-were employed to conduct examinations in the context of two different target destinations (France and China).Findings revealed that travel constraints and travel motivations generally influenced destination choice. However, it was found that PLS-SEM and fsQCA results were not compatible for some relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 90 publications
1
12
0
Order By: Relevance
“…Additionally, the study reveals that PTCs impact push and pull factors. This supports the discovery by Küçükergin et al (2021) that travel constraints affect travel motivations. The study also finds that push factors influence pull factors among senior tourists.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, the study reveals that PTCs impact push and pull factors. This supports the discovery by Küçükergin et al (2021) that travel constraints affect travel motivations. The study also finds that push factors influence pull factors among senior tourists.…”
Section: Discussionsupporting
confidence: 88%
“…Seniors face various constraints that affect their tourism participation, which must be identified and sufficiently addressed (Wen et al , 2020). Perceived travel constraints (PTCs) are factual present-focused barriers that impede tourism activities (Dale and Ritchie, 2020) and influence destination choice intentions (Küçükergin et al , 2021). In contrast to perceived travel risks (PTRs), which are potential adverse scenarios (Khan et al , 2020), PTCs are present realities (Monterrubio et al , 2021).…”
Section: Model Developmentmentioning
confidence: 99%
“…fsQCA approach was designed for small and intermediate sample sizes (<50), but recent studies have shown its application for large sample sizes (Hosany et al, 2021; Kallmuenzer et al, 2019; Kraus et al, 2018; Küçükergin et al, 2021; N. Pappas, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…As the underlying assumption of fsQCA is complex causality, 37 articles (51.4%) employed complexity theory as a leading or supportive theory. In 26 articles (36%), complexity theory was used as the leading theory, and all antecedent configurations were based on complex theory (Cheng & Xu, 2021;Han et al, 2019;Ku¨c xu¨kergin et al, 2021;Olya & Nia, 2021;Rasoolimanesh, Khoo-Lattimore et al, 2021;Rezapouraghdam et al, 2021;Robinot et al, 2021;Sim et al, 2018). Additional 11 articles (18.1%) used it as a supporting theory in combination with other theories, such as chaos theory (N. Pappas, 2017aPappas, , 2018Pappas, , 2019aPappas, , 2019bPappas, , 2021N.…”
Section: Theories Of Fsqcamentioning
confidence: 99%
“…Numerous empirical studies indicate the necessity to examine travel motivation in order to more completely understand the travel decision-making process and destination choice (Dahiya, Batra, 2016;Jević, Popesku, Jević, 2020;Küçükergin et al, 2021;Pestana et al, 2020;Seabra et al, 2014;Yiamjanya, Wongleedee, 2014). Nonetheless, identifying the motives for which tourists stay in a particular destination enables greater knowledge of the tourist profile as well as adjusting the tourist offer to their needs (Chi, Phuong, 2021;Srihadi, Sukandar, Soehadi, 2016).…”
Section: Discussionmentioning
confidence: 99%